Characterization of pre-alloyed NiTi powders produced by electrode induction-melting inert gas atomization for additive manufacturing - Wang, Junwei; He, Dingyong; Wu, Xu; Guo, Xingye; Tan , Zhen; Zhou, Zheng; Shao, Wei (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
In this research, the characteristics of Nickel-titanium (NiTi) powders produced by electrode induction melting inert gas atomization (EIGA) technique for additive manufacturing (AM) technology are investigated using various powder characterization technologies. The results show that the particle size distribution (PSD) of pre-alloyed NiTi powders prepared by EIGA has the range of 10 µm to 180 µm. The mean particle size distribution (D50) of the powder is 75 μm. The oxygen increase of the powder is only 0.005% compared to the raw rod. According to the requirements of the characteristics of the metal powder material used for AM, the powders are sieved into three categories, P1 (15-63 μm), P2 (63-150 μm), and P3 (>150 μm), respectively. The flow rates of P1 and P2 are 19.3 and 17.5 s∙(50 g)-1, respectively. The surface, cross- sectional microstructure, phase structure, and martensitic transformation temperature of the pre-alloyed NiTi powders with different particle sizes are investigated. The results show that powders of different particle sizes are primarily spherical or nearly spherical. The grain size of powders reduces with the decreasing of particle size. Both the bar stock and the powders of P1, P2, and P3 mainly exhibit the B2 phase. Comparing the powders P1, P2, and P3, the transformation temperature reduces with the decrease of particle size. A high density (99.55%) pre-alloyed NiTi specimen is successfully produced by selective laser melting (SLM) technology using P1 powders. The results indicate that the pre-alloyed NiTi alloy powder is appropriate for AM, which also has a good reference value for researchers producing AM powders. Key Words: NiTi; Powder characteristics; EIGA; Selective laser melting; Martensitic transformation temperature